2012
DOI: 10.1016/j.wneu.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Animal Glioma Models that Separately Exhibit Two Different Invasive and Angiogenic Phenotypes of Human Glioblastomas

Abstract: These animal models histologically recapitulated two invasive and angiogenic phenotypes, namely angiogenesis-dependent and angiogenesis-independent invasion, also observed in human glioblastoma. These cell lines provided a reproducible in vitro and in vivo system to analyze the mechanisms of invasion and angiogenesis in glioma progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
(47 reference statements)
1
44
0
Order By: Relevance
“…We reported that cilengitide exerts its antitumor effects by inhibiting tumor angiogenesis and invasion or by inducing apoptosis-related pathways [9], [13], [21]. We recently established two novel invasive animal glioma models (J3T-1 and J3T-2) that reflect the invasive phenotype of human malignant gliomas [22]. These models were particularly beneficial to investigate the anti-invasive effects of cilengitide [13].…”
Section: Discussionmentioning
confidence: 99%
“…We reported that cilengitide exerts its antitumor effects by inhibiting tumor angiogenesis and invasion or by inducing apoptosis-related pathways [9], [13], [21]. We recently established two novel invasive animal glioma models (J3T-1 and J3T-2) that reflect the invasive phenotype of human malignant gliomas [22]. These models were particularly beneficial to investigate the anti-invasive effects of cilengitide [13].…”
Section: Discussionmentioning
confidence: 99%
“…Two cell lines, J3T-1 and J3T-2, were developed from the J3T parental canine glioma cell line, as previously described [3]. J3T-1 and J3T-2 cells were seeded in tissue culture dishes (BD Falcon, Franklin Lakes, NJ) and cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10 % fetal bovine serum (FBS), penicillin (100 U/ml) and streptomycin (0.1 mg/ml) [2][3][4]6].…”
Section: Glioma Cell Linesmentioning
confidence: 99%
“…Therefore, understanding the mechanisms underlying angiogenesis and invasion in glioblastoma is essential for the development of novel, curative therapies. However, glioma angiogenesis and invasion are challenging to study in experimental settings since the majority of animal models fail to mimic the unique angiogenesis and invasiveness of human glioma cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a novel glioma model has been used to demonstrate, histologically, two distinct patterns of invasion – namely, angiogenesis-dependent invasion with the overexpression of angiogenesis-related genes such as those for VEGF, MMP9, hypoxia-inducible factor 1, and platelet-derived growth factor, and angiogenesis-independent invasion with overexpression of invasion-related genes such as those for integrin alpha-v beta-3, MMP2, nestin, and secreted protein acidic and rich in cysteine 19. In another aspect, SDF-1α, interleukin-6, basic fibroblast growth factor, and circulating progenitor cells are considered other escape biomarkers for antiangiogenic therapy 17.…”
Section: Molecular Mechanism Of Bevacizumab Treatment Failure On Recumentioning
confidence: 99%